Government Leadership in Public Service Delivery - Ismanudin; Diah Nurwitasari (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2025)
Leadership is a central issue in any organization that has a large role, function and responsibility so that it can determine the achievement of an organization's goals, including government organizations. However, understanding of the concept and theory of leadership is still very limited from some circles. This study aims to describe government leadership in public administration from a literature study perspective. The results of this study indicate that conceptually leadership has a role and function that determines the achievement of government organizational goals. For this reason, a good understanding is needed for government administrators and the community regarding aspects of leadership along with their roles and functions, government leadership theory, and public services.